Advancing Patient Outcomes through Collaborative Care: A Narrative Review of Evidence from Integrated Behavioral Healthcare : DOI: https://doi.org/10.46405/ejms.v6i9.546 - Ahmed , MD. Faisal; Jaman , Abdullah; Barman , Mukta; Iloanusi , Chukwuagoziem; Muna, Maharaj Khan; Arefine , Rezoana (Europasian Journal of Medical Sciences, 2024)
This review examines the Collaborative Care Model (CoCM) within Integrated Behavioral Healthcare (IBH) to explore its impact on patient outcomes, particularly mental health and chronic disease management. CoCM works via a team approach with a focus on providing holistic care, and physical, and mental health care. The narrative review synthesizing quantitative data from systematic reviews, meta-analyses, and randomized controlled trials demonstrated the successful utilization of CoCM in reducing depressive, anxious, and post-traumatic stress disorder (PTSD) symptoms, enhancing treatment compliance; and increasing quality of life. Reflecting on the observed primary outcomes: depressive symptoms decreased by 50% based on findings from meta-analyses involving patients with depressive disorders across diverse healthcare settings, and the results revealed effective chronic illness self-management including diabetes and hypertension. CoCM also shows cost savings by improving resource utilization and curtailing hospitalization costs. Furthermore, it leads to heightened patient satisfaction and better access to the best and needed behavioral health. However, some challenges still exist as to its more extensive incorporation. These issues are elements of cost drivers such as infrastructure, human resources and differences in insurance. These barriers can be eliminated only through policy changes, improved training activities, and the application of technology to foster better implementation within limited resource environments. CoCM provides a feasible solution for enhancing the effectiveness of mental health and chronic illness treatments and decreasing the costs of service provision. Extending its use to the global setting primarily LMICs requires addressing system barriers and collective strategies that lead to fair and sustainable solutions in the delivery of health care.